Pemantauan populasi ulat grayak jagung Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) pada pertanaman jagung dan padi menggunakan berbagai jenis perangkap: Monitoring population of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) Smith (Lepidoptera: Noctuidae) in maize and rice fields using different types of trap - Ihsan Nurkomar; Ichsan Luqmana Indra Putra; Dina Wahyu Trisnawati; Fadhila Lutfiyyatul Zahra; Achmad Fauzan Dharmawan (Jurnal Entomologi Indonesia, 2026)
Spodoptera frugiperda Smith is a major invasive pest of maize and has also been reported attacking other host plants, including rice. As a migratory pest with high reproductive capacity, the population dynamics of S. frugiperda are influenced by cropping systems and host plant availability. Accurate population monitoring is a key component of integrated pest management (IPM). However, the performance of different trap types under varying agroecosystems has not been fully understood. This study aimed to evaluate the performance of different trap types (pheromone, light, and pheromone–light combination traps) in detecting S. frugiperda populations in maize and rice fields under different agroecosystem conditions. The study was conducted at four locations representing distinct agroecosystem conditions. Each location consisted of three field plots as independent replications. The number of adults captured per trap per week was used as an indicator of trap performance. The results showed that S. frugiperda populations were significantly higher in maize fields than in rice fields (p < 0.0001). A significant interaction was found between trap type and agroecosystem condition (p < 0.001). Pheromone traps recorded the highest captures under high population conditions, whereas light and combination traps performed relatively similarly under low population conditions. Light traps captured more non-target insects than pheromone traps. These findings indicate that the performance of S. frugiperda traps is context-dependent and should be adapted to the cropping system to support IPM-based monitoring strategies.